2014
DOI: 10.1364/ol.39.000910
|View full text |Cite
|
Sign up to set email alerts
|

High-power supercontinuum generation in a ZBLAN fiber with very efficient power distribution toward the mid-infrared

Abstract: We report high-power supercontinuum (SC) generation in a step-index fluorozirconate (ZBLAN) fiber with a zero-dispersion wavelength shifted to ~1.9  μm. Pumping the fluoride fiber with 2.75 W of power provided by a thulium-doped fiber amplifier, a continuous spectrum extending from ~0.85 to 4.2 μm with 2.24 W of average output power was achieved. Over 61% (1.37 W) of the total output power corresponds to wavelengths longer than 3 μm, which shows, to the best of our knowledge, the highest power conversion effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 19 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…Recently, the potential of hollow-core photonic bandgap fibers 8 combined with thulium-doped fiber (TDF) amplifiers 9 for fiber optical telecommunication in the 1910-2020 nm band was reported. Furthermore, the 2-mm spectral range is also widely used to pump holmium-doped fibers 10 or to drive nonlinear processes in the mid-infrared region 11,12 . For most of these applications, a broadly tunable narrow linewidth laser source at 2 mm is required.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potential of hollow-core photonic bandgap fibers 8 combined with thulium-doped fiber (TDF) amplifiers 9 for fiber optical telecommunication in the 1910-2020 nm band was reported. Furthermore, the 2-mm spectral range is also widely used to pump holmium-doped fibers 10 or to drive nonlinear processes in the mid-infrared region 11,12 . For most of these applications, a broadly tunable narrow linewidth laser source at 2 mm is required.…”
Section: Introductionmentioning
confidence: 99%
“…The SC evolution at wavelengths shorter than 2 μm was not investigated, mainly owing to the detection system limitations. Nevertheless, it has already been shown that using fluoride fibers it is possible to achieve a broadband SC spectrum with a short-wavelength edge below 1 μm [6], [13], [25]. Further increasing the pulse energy resulted in the fiber end-face damage.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metal fluoride, such as ZrF4-BaF2-LaF3-AlF3-NaF (ZBLAN) fiber is one of the commonly used candidates due to its technological maturity, high glass stability and transparency in the mid-IR [10]. As ZBLAN fibers typically have zero-dispersion wavelengths (ZDW) between 1.65 -1.9 μm [11,12], pumping at longer wavelengths in the anomalous dispersion region is more favorable for efficient SC generation. Pumping near 2 μm results in both an extension of bandwidth and an increase of conversion efficiency towards mid-IR wavelengths [10].…”
Section: Introductionmentioning
confidence: 99%
“…Pumping near 2 μm results in both an extension of bandwidth and an increase of conversion efficiency towards mid-IR wavelengths [10]. There have been several previous work on SC pumped with Raman shifted erbium doped fiber laser [9,11]. However, directly pumping by an ultrafast TDF laser, especially with femtosecond pulses have not been investigated.…”
Section: Introductionmentioning
confidence: 99%